Chapter 20 The Relationship Between Stress and Samhandling Some Challenges for Leaders in High- Risk Organizations - Boe, Ole (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"Military operations are very often accompanied by various levels of stress. This chapter aims to discuss the concepts and factors of stress and samhandling. The main factors are social support, self-efficacy, resilience and hardiness, implicit coordination, and character strengths. Individual factors are self-efficacy, resilience and hardiness, and character strengths. Team factors are social support, team efficacy, and implicit coordination. A model describing stress and samhandling, including the above-mentioned individual and team factors and their relations, is introduced and discussed. The conclusion is that four individual and two team factors are seen as important if one wishes to counteract the effects of stress and increase both the individual's and the team's ability to conduct samhandling when facing unforeseen incidents."